Genome-Wide Characterization of B-Box Gene Family and Its Roles in Responses to Light Quality and Cold Stress in Tomato - Bu, Xin; Wang, Xiujie; Yan, Jiarong; Zhang, Ying; Zhou, Shunyuan; Sun, Xin; Yang, Youxin; Ahammed, Golam Jalal; Liu, Yufeng; Qi, Mingfang; Wang, Feng; Li, Tianlai (Frontiers in Plant Science, 2021)
Perceiving incoming environmental information is critical for optimizing plant growth and development. Multiple B-box proteins (BBXs) play essential roles in light-dependent developmental processes in plants. However, whether BBXs function as a signal integrator between light and temperature in tomato plants remains elusive. In this study, 31 SlBBX genes were identified from the newly released tomato (Solanum lycopersicum) genome sequences and were clustered into five subgroups. Gene structure and protein motif analyses showed relatively high conservation of closely clustered SlBBX genes within each subgroup; however, genome mapping analysis indicated the uneven distribution of the SlBBX genes on tomato chromosomes. Promoter cis-regulatory elements prediction and gene expression indicated that SlBBX genes were highly responsive to light, hormones, and stress conditions. Reverse genetic approaches revealed that disruption of SlBBX7, SlBBX9 and SlBBX20 largely suppressed the cold tolerance of tomato plants. Furthermore, the impairment of SlBBX7, SlBBX9 and SlBBX20 suppressed the photosynthetic response immediately after cold stress. Due to the impairment of nonphotochemical quenching (NPQ), the excess photon energy and electron flow excited by low temperature were not consumed in SlBBX7-, SlBBX9- and SlBBX20- silenced plants, leading to the over reduction of electron carriers and damage of the photosystem. Our study emphasized the positive roles of light signaling transcription factors SlBBXs in cold tolerance in tomato plants, which may improve the current understanding of how plants integrate light and temperature signals to adapt to adverse environments.